ABOUT SCHOOLS: WHAT EVERY CANADIAN PARENT SHOULD KNOW (Author: Robert M. Stamp) and LIVING AND LEARNING IN THE FREE SCHOOL (Author: Mark W. Novak) - Henchey, Norman (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1976)
Robert M. Stamp. ABOUT SCHOOLS: WHAT EVERY CANADIAN PARENT SHOULD KNOW. Don Mills, Ontario: New Press, 1975. 177 pp. 6.95. Mark W. Novak. LIVING AND LEARNING IN THE FREE SCHOOL. Toronto: McClelland and Stewart, 1975. 137 pp. 3.95.